Scaling and intermittent properties of oceanic and atmospheric pCO2 time series and their difference in a turbulence framework - K. Robache; F. G. Schmitt; Y. Huang; Y. Huang (Nonlinear Processes in Geophysics)
In this study, the multiscale dynamics of 38 oceanic and atmospheric pCO2 time series from fixed Eulerian buoys recorded with 3 h resolution are considered, and their multifractal properties are demonstrated. The difference between these time series, the sea surface temperature data and the sea surface salinity data were also studied. These series possess multiscale turbulent-like fluctuations and display scaling properties from 3 h to the annual scale. Scaling exponents are estimated through Fourier analysis, and their average quantities were considered globally for all parameters, as well as for different ecosystems such as coastal shelf, coral reefs and open ocean. Sea surface temperature is the only parameter for which a spectral slope close to 5/3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="ba5d408bbcf130091b00ac176fd54124"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="npg-32-35-2025-ie00001.svg" width="20pt" height="14pt" src="npg-32-35-2025-ie00001.png"/></svg:svg> is found, corresponding to a passive scalar in homogeneous and isotropic turbulence. The other parameters had smaller spectral slopes, from 1.22 to 1.45. By using empirical mode decomposition of the time series, together with generalized Hilbert spectral analysis, the intermittency of the time series was considered in the multifractal framework. Concave moment functions were estimated, and Hurst indices H and intermittency parameters μ were determined in the framework of a lognormal multifractal fit. We obtained mean values of H=0.26 and 0.21, respectively, for oceanic and atmospheric pCO2 time series and μ=0.08 for both. It is the first time that atmospheric and oceanic pCO2 and their difference ΔpCO2 are studied using such an intermittent turbulence framework. The ΔpCO2 time series was shown to possess a power-law scaling with an exponent of β=1.36±0.19<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="76pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="c664dd55d59146fe99ced31a68c69282"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="npg-32-35-2025-ie00002.svg" width="76pt" height="12pt" src="npg-32-35-2025-ie00002.png"/></svg:svg>.